Aversion to the variability of pay and the structure of executive compensation contracts - Chaigneau, Pierre (Journal of Business Economics and Management, 2015)
This paper presents a new implication of an aversion toward the variance of pay (“risk aversion”) for the structure of managerial incentive schemes. In a principal-agent model in which the effort of a manager with mean-variance preferences affects the mean of a performance measure, we find that managerial compensation must be such that the variance of payments is decreasing in effort. From an ex-ante perspective, which is relevant for effort inducement, this maximizes the rewards associated to high effort, and the punishments associated to low effort. An important practical implication is that convex incentive contracts do not satisfy this necessary condition for optimality, which calls into question the practice of granting executive stock options. The paper therefore contributes to the debate on the efficiency of executive compensation.